Hierarchical interface design of jute fibers/polypropylene composites for enhanced interfacial and mechanical properties - Yang, Yun (2024)
Natural fiber reinforced plastics (NFRPs) represent a promising category of emerging materials for sustainable industrial development owing to their renewability, degradability, and lightweight. However, the polarity mismatch between the fibers and polymer matrices weakens the mechanical properties of NFRPs. To address this issue, a novel hierarchical interface design was proposed here through the co-modification of silane coupling agents (SCAs) and zinc oxide nanorods (ZnO NRs), which exhibits not only high efficiency but also low energy consumption and environmental friendliness. Specifically, the hierarchical interface design was demonstrated on jute fibers (JFs)/polypropylene (PP) composites, where the JFs/ZnO interfaces were chemically bonded through complexation, chelation, or coordination using various SCAs; meanwhile, the ZnO/PP interfaces were physically bonded by interlocking effect. The experimental testing results indicated the exceptional mechanical properties of modified JFs and their composites. The JFs modified with 3-glycidyloxypropyltrimethoxysilane (KH560) and ZnO NRs exhibited an increase of 34.3% and 55.8% in single-fiber tensile strength and tensile modulus, respectively, compared to sololy ZnO coated JFs, and also showed an augment of 30.8% in the interfacial shear strength with PP resin. Thus, the transverse and longitudinal tensile strength of JFs/PP composites with combined modification of KH560 and ZnO NRs were 19.2% and 46.5% higher than untreated ones. The interfacial enhancement mechanism was ascribed to the synergistic effect of chemical bonding and physical interlocking, as revealed by molecular dynamics simulation and observation of fracture morphologies. The findings offer a cost-effective solution for developing JFs/PP composites with superior interfacial and mechanical properties, thereby promoting the practical applications and value of NFRPs.